KEUNTUNGAN DAN KERUGIAN FLEXIBLE PAVEMENT DAN RIGID PAVEMENT - Dwi Sri Wiyanti (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2011)
Abstract Pavement is a hard structure that is placed on the subgrade and functionate to hold the traffic weight that passes through. Based on its binding material, pavement construction can be distinguished into flexible pavement and rigid pavement. Flexible pavement consist of surface course, base course, subbase course, and subgrade. Rigid pavement consist of concrete slab and base course (can be not exist) on the subgrade. The main differentiations of those two kind of pavement can be seen from their type of binding, repetition of the load, depression of the subgrade, and depression of the pavement. From its main differentiations each kind of pavement has its own profits and losses. In choosing which kind of pavement that will be used, it is recomended to compare flexible pavement and rigid pavement based on their profits and losses. Key word : Profits, Losses, Flexible Pavement, Rigid Pavement